Alle pendici del Monte Testaccio (Roma): il contesto di via Galvani 40 - Bassoli, carlotta; Contino, Alessia (Rei Cretariae Romanae Fautorum Acta, 2024)
The investigated area is located in a basement of the one of many caves identified at the foot of Monte dei Cocci, excavated starting from the second half of the 17th century and used for storing wine. The investigation, which identified a part of the ancient slopes of the mountain, involved the systematic collection of all the fragments on which a selection was subsequently carried out. In total, 3185 ceramic fragments were collected and classified, mostly transport containers. The most quantitatively represented group of amphorae is coming from Baetica and Tarraconense, the second most represented group is the oriental production, coming mainly from the Aegean. The context has yelded 10 stamps and 8 tituli picti on Baetican, Tarraconensis, Laietan and Eastern amphorae.